2014
DOI: 10.1159/000356657
|View full text |Cite
|
Sign up to set email alerts
|

Co-Incubation of Human Spermatozoa with Anti-VDAC Antibody Reduced Sperm Motility

Abstract: Background: Voltage-dependent anion channel (VDAC), a channel protein, exists in the outer mitochondrial membrane of somatic cells and is involved in multiple physiological and pathophysiological processes. Up until now, little has been known about VDAC in male germ cells. In the present study, the relationship between VDAC and human sperm motility was explored. Methods: Highly motile human spermatozoa were incubated in vitro with anti-VDAC antibody. Total sperm motility, straight line velocity (VSL), curvilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In addition, velocity parameters (VSL, VAP and VCL) significantly decreased at pH 6.2 and 5.2, which was consistent with the result of motility. Additionally, fertilization success was always found to be correlated with VSL, VAP and VCL in the chicken, turkeys and human [ 31 33 ]. Our study showed that in acidic environments (pH 5.2 and 6.2), most of the sperm, which stayed within 1 cm from basal part of capillary pipettes, swam in situ , and few of them swam upward in the sperm penetration meter test.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, velocity parameters (VSL, VAP and VCL) significantly decreased at pH 6.2 and 5.2, which was consistent with the result of motility. Additionally, fertilization success was always found to be correlated with VSL, VAP and VCL in the chicken, turkeys and human [ 31 33 ]. Our study showed that in acidic environments (pH 5.2 and 6.2), most of the sperm, which stayed within 1 cm from basal part of capillary pipettes, swam in situ , and few of them swam upward in the sperm penetration meter test.…”
Section: Discussionmentioning
confidence: 99%
“…Flagellar beating and swimming velocity is triggered and maintained by Ca influx [Carlson et al 2003;Liu et al 2014;Ren et al 2001;Yoshida et al 2003]. Plasma membrane calcium pumps depend on sufficient ATP [Cartwright and Neyses 2010] and we hypothesized that ATP deficiency might result in impaired [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…Absorbance was measured at 450 nm using a microtiter plate reader (Bio-Rad, USA). Cellular ATP levels were determined using an ATP Assay Kit (Beyotime Institute of Biotechnology, China) according to the manufacturer's protocol [16].…”
Section: Cmec Isolation Culture and In Vitro Iri Assaymentioning
confidence: 99%